2015
DOI: 10.7224/1537-2073.2014-040
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Dalfampridine Extended Release 5 and 10 mg in Multiple Sclerosis

Abstract: Background: Dalfampridine extended-release (ER) tablets, 10 mg twice daily, have been shown to improve walking in people with multiple sclerosis. We evaluated the safety and efficacy of dalfampridine-ER 5 mg compared with 10 mg.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 13 publications
1
25
0
1
Order By: Relevance
“…Because of the clinical implications of UTIs in people with MS, an objective of this study was to examine the increased risk of confirmed UTI as part of a postmarketing commitment. measures and the overall tolerability have previously been described [15]. Briefly, the study included a 1-week screening and 4-week treatment period (visit 1: randomization and baseline safety and efficacy assessments; visit 2: week-2 interim assessments; and visit 3: week-4 assessments and study completion).…”
Section: Introductionmentioning
confidence: 99%
“…Because of the clinical implications of UTIs in people with MS, an objective of this study was to examine the increased risk of confirmed UTI as part of a postmarketing commitment. measures and the overall tolerability have previously been described [15]. Briefly, the study included a 1-week screening and 4-week treatment period (visit 1: randomization and baseline safety and efficacy assessments; visit 2: week-2 interim assessments; and visit 3: week-4 assessments and study completion).…”
Section: Introductionmentioning
confidence: 99%
“…A detailed description of the patient selection and methodology in this study has been previously published. 6 In brief, in this randomized, double-blind, placebo-controlled, parallel-group study, after a 1-week screening period, participants were randomly assigned, in a 1:1:1 ratio, to receive dalfampridine ER 5 or 10 mg or placebo, BID for 4 weeks. The study was performed in accordance with the revised Declaration of Helsinki.…”
Section: Patients and Methods Study Designmentioning
confidence: 99%
“…4 Dalfampridine ER is a broad-spectrum inhibitor of voltage-gated potassium channels, with a putative mechanism of action of improving actionpotential conduction in the demyelinated axons that are characteristic of MS. 5 To fulfill a postmarketing regulatory commitment, a study was performed to evaluate the efficacy and safety profile of dalfampridine ER 5 mg BID, relative to the approved dose of 10 mg BID, to those of placebo was performed. 6 The primary efficacy end point of the original study, change from baseline on the timed 25-foot walk (T25FW) test at 4 weeks after the start of treatment, was not significantly different between either of the active treatment groups and the placebo group. However, in a post hoc analysis of mean data from all study visits, walking speed was significantly increased in the 10-mg BID dose group compared with that in the placebo group (nominal P ¼ 0.014).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…In einer nachfolgenden Dosisvergleichsstudie mit 2 × 5 mg versus 2 × 10 mg Fampridin über 4 Wochen war die über alle verfügbaren Messungen gemittelte Ganggeschwindigkeit nur mit 2 × 10 mg Fampridin gegenüber Placebo signifikant gesteigert. Allerdings scheint die Verbesserung der Ganggeschwindigkeit unter Fampridin nicht derjenigen eines Gangtrainings überlegen zu sein [27]. In weiteren Studien waren auch Aufstehen (Timed-Get-up-and-Go-Test), Gleichgewicht (Berg Balance Scale) und die MSWS-12 nach 6 Monaten Fampridin im Vergleich zu Placebo signifikant verbessert [6].…”
Section: Caveunclassified